PENGARUH PENDEKATAN DEEP LEARNING BERBASIS SCRATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJAR IPAS KELAS V DI SDN 3 LEMBAK - Munawwaroh Gumayyah; Aquami; Middya Botty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This research is motivated by the low learning outcomes of fifth-grade students in the science subject at SDN 3 Lembak, which is caused by the lack of variety in approaches and learning media used in the learning process. This study aims to determine student learning outcomes before and after the implementation of the Scratch-based deep learning approach and to determine the effect of this approach on student learning outcomes. The study used a quantitative method with a One Group Pretest-Posttest design. The subjects were 20 fifth-grade students of SDN 3 Lembak. Data collection techniques were carried out through tests in the form of pretests and posttests given before and after the treatment. The data obtained were analyzed using statistical tests to determine differences in student learning outcomes before and after the implementation of the Scratch-based deep learning approach. The results showed that the implementation of the Scratch-based deep learning approach was able to improve student learning outcomes in the science subject. This was indicated by an increase in the average posttest score compared to the average pretest score and the results of statistical tests that showed a significant effect on student learning outcomes. Thus, the Scratch-based deep learning approach can be used as an effective learning alternative to improve student learning outcomes in the science subject.